Pemanfaatan Limbah Sekam Padi Sebagai Bahan Dasar Pembuatan Briket Arang - Ahmad Hafizullah Ritonga; Denny Akbar Tanjung (Pelita Masyarakat, 2019)
Rice husk waste has been thrown away and burned without any use, it has the potential to cause environmental pollution. This rice husk can actually be used, for manufacture of briquettes, but the lack of knowledge and skills of the people about processing rice husk waste into briquettes. The process of making briquettes does not require high technology and low cost. The training in manufacturing of charcoal briquettes is very useful which aims to make people in the area able to utilize rice husk waste to become a product of sustainable technology, namely charcoal briquettes which can be used as an alternative fuel instead of BBM, and also minimize the occurrence of environmental pollution. These activities include (1) socializing the using of rice husk into charcoal briquettes; (2) training to manufacture of chimneys to burn rice husk; (3) processing of rice husk into charcoal; (4) manufacturing charcoal briquettes; (5) applying the use of briquettes as fuel. These socialization and training activities have been successfully carried out in accordance with the planned activities that have been prepared, and received good reception from the local villagers seen from their presence and involvement in activities, and succeeded in providing special skills for local residents, especially farmers who were directly involved in making briquettes.